Smart IT Management Evaluation in Intelligent Environment Computing. (27th September 2015) - Kim, Yanghoon; Hwang, Heon; Chang, Hangbae
Abstract : As everything is integrated with smart IT technologies due to their rapid growth and enhancement, smart IT technologies and environments have been pervading business environments in the way of intelligent environment computing and have been embedded in them. Accordingly, it is expected that the number of information devices used and utilized in industry would be increased significantly. Therefore, intracompany smart IT management becomes more important to efficiently utilize information devices increased rapidly due to introduction of intelligent environment computing. In addition, there is a need of understanding corporate smart IT management levels in the intelligent environment computing to establish information strategies for flexibly responding to internal and external environment factors being varied rapidly by corporate policies. Therefore, this study would like to analyze management levels for smart IT to improve corporate smart IT application capabilities in the intelligent environment computing. In detail, it designed a conceptual system for analyzing smart IT management levels to analyze 282 companies. And it suggested a direction of utilizing smart IT efficiently and properly in the intelligent environment computing through comparative analysis of the smart IT management level cases analyzed by other organizations.